Investigating Aggressive Behavior among Urban Adolescents: The Role of Parental Monitoring and the Dark Triad Personality - Catherine Vanessa Permana; Ni Putu Adelia Kesumaningsari; Surya Prawira Adinata (Universitas Ahmad Dahlan, 2023)
Aggressive behavior is an intentional act of hurting other people or creatures, either verbally or non-verbally, and can be influenced by various internal and external factors. Therefore, this study aimed to determine the relationship between parental monitoring and dark triad personality in relation to aggressive behavior in adolescents. The participants were 150 adolescents aged 12 to 15 years, who filled out the Parental Monitoring Scale (PMS), Short Dark Triad (SD-3), and Buss-Perry Aggression Questionnaire (BPAQ). The results showed that parental monitoring and dark triad personality, consisting of machiavellianism, narcissism, and psychopathy, collectively predicted aggressive behavior in adolescents (R2=0.441, p<0.05). In comparison to parental monitoring, the dark triad personality was a stronger predictor of aggressive behavior. Machiavellianism contributed the most to aggressive behavior in adolescents (29%). The implications of this study served as a valuable reference for parents, counselors, and communities, emphasizing the importance of addressing and preventing aggressive behavior among adolescents.